Inquiry-Based Learning for Physics Courses within the Russian Schooling System - Olga V. Lebedeva (National Research Mordova State University, 2017)
Introduction: this article discusses the didactic and methodological problems of implementing inquiry-based learning into Russian schools. It is especially relevant now as new educational standards were introduced. Literature review showed that while implementing inquiry-based learning schools in different countries face the same difficulties, some of which are related to teachers’ professional competence. The goal of the research is to develop a theoretical framework for inquiry-based learning which includes patterns, educational process design, as well as an algorithm for teachers’ work. Materials and Methods: the research analyzed normative documents for school education, research and methodological literature on research-based education. We also designed the process of research-based education for the school course of physics. Summative, research and formative teaching experiments were carried out, as well as questionnaire survey and interviews for physics teachers. We also tested the students of Nizhny Novgorod schools and first-year students of Lobachevsky State University of Nizhny Novgorod. Results: the result of the research is the didactic basis for the theory of modelling inquiry-based learning in physics. We stated the patterns of learning process, algorithm for teachers and a generic model of a research class. Pedagogical experiment (implementing this model) showed a statistically reliable increase in the required standard of students’ research skills. Discussion and Conclusions: the study proved the efficiency of the proposed models for inquiry-based learning. The practical value of the work is a developed algorithm of educational process that can be used to increase teachers’ competence in inquiry-based teaching based on the integration of school and college level education.